Discourse in Legal Contexts: Its Concept, Patterns and Functions - Hasan, Alaa Abdo Salem; Al-Rashed, Amal Abdullah (Arts for Linguistic & Literary Studies, 2024)
This research delves into discourse within the framework of legal proceedings, scrutinizing terminology and its associated concepts, as well as patterns and their functionalities. Throughout this exploration, theoretical quandaries are unearthed, revealing intersections and varying perspectives. The study is structured with an introduction, a preface, three main sections, and a conclusion. The preface briefly touches upon the concept of discourse, its determinants, and operational mechanisms. The first section delves into the notion of legal language and its defining traits, while the second section broadens the scope to encompass legal discourse in its entirety, dissecting its patterns, functions, and the distinction between oral and written forms. The third section focuses specifically on the patterns and functionalities of criminal discourse. The research concludes by highlighting significant findings, notably addressing the challenge of reconciling legal and linguistic perspectives on the nature of legal language. It proposes a comprehensive concept that encompasses all verbal and written legal interactions, elucidating how the interplay between language and law across various legal procedures yields distinct discourse patterns with unique characteristics, nature, and functional objectives.